2017
DOI: 10.3329/bjar.v42i2.32823
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in maize inbreds under excess soil moisture condition

Abstract: Genetic diversity study was done in 64 maize inbreds grown under excess soil moisture condition.The genotypes were grouped into eight clusters. It was observed that all intercluster distances were larger than all intracluster distances. Such results indicated that genotypes included within a cluster had less diversity among themselves but wider genetic diversity among the inbreds of different clusters. The highest inter cluster distance was observed between cluster IV & VII followed by IV & V , IV & VIII, II &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The character plant height showed highest percent contribution (28.48) towards total genetic divergence followed by number of kernels per row (13.67), ear height (8.82), number of kernel rows per ear (7.47), grain weight per plot (7.41), 100 seed weight (6.94), ear length (4.98), days to 50% silking (3.91), ear diameter (3.64),ear per plot (3.1), days to 50% anthesis (2.9), plant population (2.76), yield per plant (2.63),number of surface roots (2.49) and number of nodes bearing brace roots (0.81). These results are in agreement with that of Hoque et al (2017) and Maruthi et al (2015) who also identified above said characters as the principal components contributing maximum to the total variation in maize. These characters should be given importance for selecting diverse parents for water logging resistance breeding programmes in maize (Narayan et al, 2015).…”
Section: Resultssupporting
confidence: 92%
“…The character plant height showed highest percent contribution (28.48) towards total genetic divergence followed by number of kernels per row (13.67), ear height (8.82), number of kernel rows per ear (7.47), grain weight per plot (7.41), 100 seed weight (6.94), ear length (4.98), days to 50% silking (3.91), ear diameter (3.64),ear per plot (3.1), days to 50% anthesis (2.9), plant population (2.76), yield per plant (2.63),number of surface roots (2.49) and number of nodes bearing brace roots (0.81). These results are in agreement with that of Hoque et al (2017) and Maruthi et al (2015) who also identified above said characters as the principal components contributing maximum to the total variation in maize. These characters should be given importance for selecting diverse parents for water logging resistance breeding programmes in maize (Narayan et al, 2015).…”
Section: Resultssupporting
confidence: 92%